Mouse-specific residues of claudin-1 limit hepatitis C virus genotype 2a infection in a human hepatocyte cell line - Haid, Sibylle; Windisch, Marc Peter; Bartenschlager, Ralf; Pietschmann, Thomas (Journal of virology, 2010)
Recently, claudin-1 (CLDN1) was identified as a host protein essential for hepatitis C virus (HCV) infection. To evaluate CLDN1 function during virus entry, we searched for hepatocyte cell lines permissive for HCV RNA replication but with limiting endogenous CLDN1 expression, thus permitting receptor complementation assays. These criteria were met by the human hepatoblastoma cell line HuH6, which (i) displays low endogenous CLDN1 levels, (ii) efficiently replicates HCV RNA, and (iii) produces HCV particles with properties similar to those of particles generated in Huh-7.5 cells. Importantly, naïve cells are resistant to HCV genotype 2a infection unless CLDN1 is expressed. Interestingly, complementation of HCV entry by human, rat, or hamster CLDN1 was highly efficient, while mouse CLDN1 (mCLDN1) supported HCV genotype 2a infection with only moderate efficiency. These differences were observed irrespective of whether cells were infected with HCV pseudoparticles (HCVpp) or cell culture-derived HCV (HCVcc). Comparatively low entry function of mCLDN1 was observed in HuH6 but not 293T cells, suggesting that species-specific usage of CLDN1 is cell type dependent. Moreover, it was linked to three mouse-specific residues in the second extracellular loop (L152, I155) and the fourth transmembrane helix (V180) of the protein. These determinants could modulate the exposure or affinity of a putative viral binding site on CLDN1 or prevent optimal interaction of CLDN1 with other human cofactors, thus precluding highly efficient infection. HuH6 cells represent a valuable model for analysis of the complete HCV replication cycle in vitro and in particular for analysis of CLDN1 function in HCV cell entry.
Gesehen am 03.03.2023